Are They Athletes? A Self-Assessment of Athletic Identity Measurement and Perceived Benefits of Collegiate Esports Participants. Issue 2 (October 2021) - Buzzelli, Armand; Draper, Jason
Collegiate esports is a rapidly growing entity that is managed differently across campuses, with oversight taking place in athletic departments, campus recreation departments, student affairs, and to a lesser degree, academic departments. Esports has the potential to support the recruitment and retention of students while supporting the academic mission of universities through co-curricular opportunities in a variety of subject areas. Despite the broad existence of peer-reviewed research debating the consideration of esports as a sport, limited research is available that asks esports participants if they view themselves as athletes. A total of 120 participants completed a survey instrument that included items from the Athletic Identity Measurement Scale-Plus and the Quality and Importance of Recreational Services instruments. From the collegiate esports players included in this research, we see a complex picture of student-athletes emerging.